An INFORMATION TECHNOLOGY GOVERNANCE AUDIT PLANNING CALIBRATION LABORATORY USING COBIT 2019 - angga wijaya (Fakultas Ilmu Komputer, Unversitas Muhammadiyah Riau, 2020)
As a calibration laboratory that has been accredited by the KAN Institute, BSML Regional II is obliged to implement a quality system. In response to the demands of information technology developments, KAN calls on calibration laboratory organizations to develop information technology and its management. Information technology governance audit, besides functioning to identify management mismatches, also functions to optimize performance so that the company's vision and mission can be achieved. COBIT 2019 as the latest edition of ISACA's framework makes improvements in terms of goal cascading using design factors so that planning / design audits will be more precise. This research produces a planning of information technology governance audit activities in the calibration laboratory, in this case BSML Regional II.